Agriculture as an Urban Activity: Social Forces in Winnipeg's Grain Industry - Novek, Joel (Urban History Review / Revue d'histoire urbaine, 1987)
The prairie grain industry has been extensively analyzed in terms of its economic impact but it also deserves scrutiny as a social institution which has been influenced by social and political factors. Chief among them is the conflict between prairie producers and private grain merchants which has led to the industry being divided into privately-owned and producer cooperative segments. In addition, extensive political intervention has led to the growth of a substantial publicly controlled segment.All segments of the industry are being affected by long term trends toward consolidation, bureaucratization and the application of advanced information technology. These activities point more to stability rather than rapid growth for Winnipeg's economy. They also indicate an emerging division of labour in which urban based organizations perform a variety of service activities for a geographically dispersed production hinterland.